Identification of Problem Solving Abilities of Deaf Students In Pictorial Math Problems - Zahid Abdush Shomad; Zaenuri Zaenuri; Adi Nur Cahyono; Bambang Eko Susilo (Universitas Negeri Semarang, 2022)
Abstrak. Deaf students have limitations in language, so they have difficulty in solving story problems. The use of mathematical problems with pictures makes the information about the questions readable with the use of few terms and language. However, it is possible for deaf students to have different terms so that they have different misconceptions or ways of solving them. the approach used is qualitative research with case studies. The subjects involved were deaf students without mental and intelligence disorders as many as 5 students at SLB-B YPPALB Magelang City. Collecting data using written tests and interviews which are then analyzed through triangulation of sources. The results obtained are deaf students are not familiar with pictorial questions so it takes longer. Based on the indicators of problem solving ability, deaf students have difficulty in interpreting the meaning of the questions so that there are errors in working on the questions. Errors that occur are errors in the concept used, calculating errors, and errors in the use of formulas.